A construção do marco legal para a (i)migração no Brasil: uma análise da transição paradigmática a partir da experiência do município de São Paulo (2013-2016) - Brasil, Paula Zambelli Salgado (2017)
In the 21st century, international flows and migratory processes intensified in quantity, as well as in degree of complexity. The Latin American countries are no longer just lands of emigration whose people move towards the northern hemisphere, particularly USA, Europe and Japan, but are also, at the same time, final destinations, corridors, or transit locations for different migratory dynamics outside or within the borders of the continent. This is due, in part, to the hardening of US and European migration policies, but also to the facilities provided by means of transportation and communication technologies, coupled with regulatory openings in several South American countries, as well as the incipient movement of regional integration, caused by Mercosur and Unasur. In this context, special attention is given to research that deals with themes that combine international migrations and their processes, with the professional insertion of migrants; mobilizations of the associative tissue and the formation of networks as a response to the economic crisis; the increasing feminization of migratory movements and their implications; the issues of racial discrimination or the discussions aimed at the national identity and the configuration of new perspectives for citizenship; or those that deal with the interrelationship between the migratory categories (whether voluntary, forced or mixed) and the need to (re)formulate the legal framework and public policies with attention to the specific needs of each of these migratory categories. This work intends to analyze the last two outstanding themes, considering the strong migratory flow experienced by Brazil in the last years and the (in)capacity of the current juridical order to deal with this new social reality, since it has two different mechanisms for reception and hosting: one aimed at people in refugee conditions, which serves as an example to other countries, since it is humanistic and based on the promotion and guarantee of human rights, and another one for the voluntary migrants, inherited from a regime of exception, restriction and selection. Faced with this tension, this research intends to discuss the intrinsic ideological and political issues involved in the process of federal legislative change and to verify what can be learned from the experience of the city of São Paulo, in the implementation of the law and policies to (im)migrants, from 2013 to 2016.